Developing an Augmented Reality–Based E-Book Integrating Multiple Intelligences and Tawhid (ARMI Meta E-Book) for Early Childhood Education - Amelia, Lina; Lisfa, Ridhatul; Nurjannah, Nurjannah; Rahmadhani, Nadia; Suwandi, Cut Intan (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
This study aimed to develop and validate an Augmented Reality–Based E-Book integrating Multiple Intelligences and Tawhid (ARMI Meta E-Book) for early childhood education. Employing a Research and Development approach using the ADDIE model, the study involved expert validation, teacher practicality assessment, and field trials with children aged 5–6 years. Data were collected through validation questionnaires, teacher responses, observations, and documentation. The results demonstrated very high validity from content and language experts (100%) and strong media validity after revision (88%). Practicality testing showed that 87.5% of teachers rated the e-book as very practical and easy to use. The ARMI Meta E-Book integrates augmented reality, multiple intelligence stimulation, and tawhid values through dual 3D exploration (online and offline), supporting cognitive, social-emotional, and spiritual development. This study contributes an innovative, holistic learning medium that supports transformative early childhood education in the digital era.